Phytochemical Analysis and antioxidant activity from Phanera semibifida stem and leaves extracts using LC-MS/MS - MEYLA SUHENDRA; BERRY JULIANDI; HUDA SHALAHUDIN DARUSMAN; SITI SADIAH; FITMAWATI FITMAWATI; SRI BUDIARTI; PUJI RIANTI (Society for Indonesian Biodiversity, 2025)
Phanera semibifida is a forest plant that contains metabolites such as flavonoids, terpenoids, saponins, and tannins. Lingga Malay ethnic uses P. semibifida stem as the main ingredient in health potions. Based on this primary evidence, P. semibifida has potential medicinal uses. However, studies on metabolite content and bioactivity screening of the stem and leave extract P. semibifida are still limited. This research aimed to identify the phytochemical profile and  bioactivity screening of the P. semibifida stems and leaf extract. The sample was extracted using 96% ethanol with maceration methods. The chemical content was identified using LC-MS/MS methods. Antioxidant potential was eval__uated with DPPH methods. Based on LC-MS/MS analysis, 26 compounds were identified from stem extract, and 24 compounds were identified from leave extract. The compound originates from seven compound groups: carboxylic acid,  flavonoid, phenolics, polifenol, terpenoid, Tricarboxylic acid, and Humulonoid. Carboxylic acid is the most commonly obtained compound in this research. The compounds identified in the stem extract differ from those in the leaf extract. Quercetin-3'-glucuronide, Apigetrin, and Glucogallin are only found in the stem extract, whereas Salicylic acid is only found in the leaf extract. Many researchers report that the group compound has potential as Antioxidants, antiviral or antimicrobial, anti-vitiligo, anticancer or antitumor, anti-inflammatory, antidepressant, and anti-diabetic. The antiradical activity assay revealed that the stem extract had the highest activity, with an IC50 of 9.091 ppm. The IC50 data indicated that higher quantities of flavonoid components could increase antioxidant activity.